928 Current Practice in The Investigation and Management of Post-Operative Ileus. (12th October 2021) - English, C; Jakes, A; Wheatstone, S
Abstract: Introduction: Post-operative ileus is non-obstructive impairment of gastrointestinal motility after surgery. Treatment involves nil-by-mouth, correction of electrolytes and stopping aggravating medications. There is no current national/trust guideline for investigation and management of post-operative ileus. Aim: To assess current practice in investigation and management of post-operative ileus on surgical wards at St Thomas's Hospital. Method: All patients with a diagnosis of post-operative ileus on surgical wards between November - December 2020 were identified. Their clinical notes were reviewed, and common themes explored. Results: 16 patients were diagnosed with post-operative ileus. 12 (75%) patients were male, with a median age of 60 (IQR: 28). 10 (63%) were open procedures, majority being colorectal (10; 63%), cardiothoracic (3; 19%), urological (2; 13%), vascular (1; 6%) operations. Average time between operation and diagnosis was 5.2 (range: 2-14) days. Bowel sounds were auscultated in only 2 (12.5%) patients at initial assessment. 8 (50%) patients had imaging to confirm diagnosis (AXR; 5, CT scan; 4). Majority (15; 94%) of patients had serum magnesium and potassium checked at diagnosis. All patients with serum potassium <4.0mmol/L (5) and magnesium <0.7mmol/L (2) had intravenous supplementation. 14 (88%) were administered Hartmann's solution. 10 (63%) patients were made nil-by-mouth and 15 (94%) had a Ryles tube inserted. 2 (12.5%) patients were prescribed a prokinetic, and only 2 had either opioids or laxatives stopped. No patients were offered gum. Conclusions: There is apparent clinical variation in investigation and management of post-operative ileus. We plan to develop an evidence-based trust guideline to reduce unwarranted clinical variation.